Empowering Trainers, Transforming Lives: An Impact Study of the BPSU Hope Behind Bars Train the Trainers Program - Gabor, Bernadeth B. (CV. Literasi Indonesia, 2025)
The Bataan Peninsula State University’s HOPE Behind Bars project, a 14-year-old initiative, has had a profound impact on the lives of Persons Deprived of Liberty (PsDL) in Bataan. As the project expanded to the entire Region 3, there was a growing need for additional trainers to ensure the program's sustainability. To address this, the university's HOPE Behind Bars team implemented a Train the Trainers (TOT) program, equipping Bureau of Jail Management and Penology (BJMP) personnel in charge of the welfare and development of PsDL with essential skills in various vocational areas, including Housekeeping, Food Processing, Bread and Pastry, Tile Setting, and Masonry. The TOT program not only helped the BJMP sustain the training and assist PsDL in passing national assessments but also empowered the personnel themselves. Many of the trained trainers were able to start their own businesses, receive promotions, and gain recognition for their contributions. This study aimed to evaluate the impact of the BPSU HOPE Behind Bars TOT program, utilizing both quantitative and qualitative methods. Structured questionnaires were employed for the quantitative analysis, while interview guides were used to gather in-depth insights from the participants. The findings of the study highlighted the project's success in equipping trainers with essential skills, fostering a supportive learning environment, and promoting effective PDL rehabilitation. The results will serve as a foundation for an enhancement program, further empowering Persons Deprived of Liberty in terms of their welfare and development.